USO DO MECANISMO DE DESENVOLVIMENTO LIMPO (MDL): UMA VISÃO DE NEGÓCIOS PARA PROJETOS AMBIENTAIS. ESTUDO DE CASO DE APLICAÇÃO DE MDL EM UM ATERRO SANITÁRIO NO ESPÍRITO SANTO - Marchezi, Roberta da Silva Monteiro (2009)
This study intends to evidence the possibility of an environmental project, deriving from a social-environmental strategy, to be considered as a business for companies, thus allowing the attainment of benefits such as competitive advantage, improvement of image and increase of yield on sanitary landfills. The environmental project used as basis in this dissertation is the Clean Development Mechanism (CDM), which is an instrument of flexibilization foreseen in article 12 of the Kyoto Protocol and which is of utmost importance for the developing countries, seeing that it searches for technology transfer and inserts these countries in the emergent carbon market, on top of promoting the mitigation of climatic changes, which is its main objective. The circumstances and the context presented in this work generate strong trends of how sanitary landfills must be constituted, be organized and managed, in such a way to obtain greater financial returns and competitiveness. The trade on carbon credit is becoming the most promising source of funding for the environmental area, being the CDM an excellent chance of implementing both new technologies and new qualifications, and additionally making it possible that sanitary landfills receive resources of foreign companies or countries interested in obtaining Certificates in Emission Reductions (CER). As he is of public knowledge, there are still many issues and problems faced by Brazilian cities in handling the final destination of its residues, and therefore the sales of Certificates in Emission Reductions can help financing the sanitary landfills. For the deepening of the study and hence obtaining the answers to the identified questions, a case study was carried through about the experience of one landfill located in the State of the Espirito Santo. The CDM project implemented by Marca Ambiental is the result of a socialenvironmental strategy, being the same still in phase of adjustments and issuance of the (CER), but several benefits have already been obtained. Based on acquired information, we could verify that it is possible to get competitive advantage through environmental projects, in the scope of the CDM, and evidence the necessity of the companies to have clear and implemented social-environmental strategies.